Design of “Chicken Move Tracking” Integrated System as an Innovation to Support a Sustainable Economy in Pitiek Racing Sidomulyo Distribution - Putri Noviana Nih Pratama; Meli Novianti Rohali; Angga Adit Saputra (Jurnal Multidisiplin Madani, 2023)
Pitiek Balap Sidomulyo is a business engaged in the distribution of chickens. The scope of this business market is in the form of restaurants, markets, hotels, and chicken slaughterhouses in Yogyakarta and Jakarta. Based on the observed data, problems were found, namely in the shipping and distribution management sections that were not optimal. The purpose of this study is to analyze and design an information system to support a sustainable economy in the distribution of chicken from distributors to consumers. The methods used are observation, interviews and literature studies which are then made into an information system design using the Business Process Model and Notation (BPMN), and the Unified Modeling Language (UML). The design of this information system is expected to be able to increase the effectiveness of the Supply Chain Management of chicken distribution in the Pitiek Balap Sidomulyo business